Propriedades fotoluminescentes e fotocatalíticas dos tungstatos de ferro e manganês - Almeida, Marcio Aurélio Pinheiro (2013)
MnWO4 and FeWO4 compounds were synthesized, employing AOT, SDS, CTAB, EG, and PEG 200 as surfactants agents, which was proved by X ray diffraction. Furthermore, these compounds were also characterized by vibrational spectroscopy in the infrared, Raman spectroscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The SEM images showed that the morphology of the compounds of MnWO4, were changed to plates (AOT and SDS) and particles (CTAB, PEG and EG 200) when the surfactants were employed in the reaction, while the compound achieved without the use of surfactants, showed morphology of rods. The band gap values of band gap found for the compounds of MnWO4 ranged from 2.1 to 2.9 eV, while the values of "band gap" for compounds of FeWO4 were much smaller, ranging between 1.6 to 2.2 eV, and these values were lower than the values of band gap of the compounds obtained without the use of surfactants. These behaviors can be attributed to the presence of defects. The data photoluminescence in general all compounds obtained with surfactants, both of MnWO4, as those of FeWO4, showed photoluminescence intensity far greater than the reference compounds (MnWO4 and FeWO4) which can be assigned to different types of surface defects and interactions between different clusters. The photodegradation of the dyes rhodamine B and rhodamine 6G by nanocrystals MnWO4 proves ineffective, while, FeWO4 compounds were more effective, giving greater emphasis to the compounds obtained with EG and PEG 200.